Oxygen-vacancy-enriched copper-based nano material and preparation method and application thereof
By using alcohol solvents and copper salt solutions on hydrophobic carbon paper for constant potential electrodeposition and cyclic voltammetry modification, oxygen-rich vacancies Cu/Cu2O nanomaterial was prepared, which solved the low selectivity of existing copper-based catalyst C2+ products. Problem, efficient CO2RR and low by-product generation are achieved.
Patent Information
- Application Number
- CN202411477310.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-10
AI Technical Summary
The existing copper-based catalysts have low selectivity for C2+ products in CO2RR, and the selectivity of by-product CO is high, which hinders the industrial application of C2+ products.
Alcohol solvents are used as hydrophilic agents and copper salt solutions are used as electrolytes to conduct constant potential electrodeposition on hydrophobic carbon paper, and oxygen-rich vacancies Cu/Cu2O nanomaterials are prepared for CO2RR .
It improves the selectivity of C2+ products, reduces the generation of CO by-products, and achieves efficient CO2RR. It has simple process and mild conditions, which is suitable for large-scale production.
Smart Images

Figure CN119287468A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemical functional materials, and in particular to an oxygen-vacancy-rich copper-based nanomaterial and a preparation method and application thereof. Background Art
[0002] The rapid consumption of fossil energy has produced a large amount of greenhouse gases (such as CO2), which has led to an increasingly serious greenhouse effect in the atmosphere and has had a great negative impact on the global climate. Electrocatalytic reduction of CO2 (eCO2RR) can use electricity produced by renewable energy as energy to convert CO2 into high-value-added chemicals and fuels (such as CO, HCOOH, CH4, C2H4, CH3COOH, CH3CH2OH and n-PrOH). It has the prospect of industrial application and is an effective solution to the greenhouse effect. Compared with the widely reported C1 products, C2 products (such as C2H4 and CH3CH2OH) are important chemicals with high market demand and great economic benefits. In addition, multi-carbon products are conducive to the subsequent synthesis of more complex products, thereby further improving the value of the products. Therefore, there is an urgent need to develop highly active, highly selective and simple-to-prepare CO2RR electrocatalysts.
[0003] The Cu-based catalysts currently under research can effectively convert CO2 into C 2+ products, but generally have a high selectivity for the by-product CO, which is not conducive to the subsequent utilization process. 2+ The products are often produced at higher potentials, and the competition for hydrogen evolution side reactions is intensified, which is not conducive to the production of C 2+ For example, the prior art document "Chlorine-mediated electrodeposition of hierarchical and hydrophobic copper electrocatalysts for efficient CO2 electroreduction to ethylene" (Liu. J et al., Chem. Commun., 2023, 59, 10428-10431) reported a chlorine-mediated electrodeposition copper-based catalyst, which was used to electrocatalyze the generation of C2H4 with a CO ratio of 20%. Therefore, the poor product selectivity seriously hindered the production of C2H4 using CO2RR. 2+ Industrial application of the products and development of corresponding copper-based catalysts.
[0004] Therefore, it is extremely important to develop a CO2RR electrodeposition catalyst with a simple preparation method and low selectivity for the by-product CO. Summary of the invention
[0005] The purpose of the present invention is to provide an oxygen-rich vacancy copper-based nanomaterial and a preparation method and application thereof, which can overcome the problem of existing copper-based catalysts catalyzing CO2RR to obtain C 2+ The problem of low product selectivity.
[0006] In one aspect of the present invention, the present invention proposes a method for preparing an oxygen-rich vacancy copper-based nanomaterial. According to an embodiment of the present invention, the following steps are included: in the case of an alcohol solvent as a hydrophilic agent, a copper salt solution is used as an electrolyte, constant potential electrodeposition is performed on the surface of a hydrophobic carbon paper, and the electrolyte is replaced for cyclic voltammetry current modification, wherein the potential window of the cyclic voltammetry process is -0.3 to -0.8V. Specifically, the copper salt solution and the alcohol solvent are first mixed to form a mixed solution for constant potential electrodeposition, and after the deposition is completed, it is transferred to the electrolyte required for the cyclic voltammetry process, and current modification is performed to obtain an oxygen-rich vacancy Cu / Cu2O nanomaterial.
[0007] In addition, the method for preparing an oxygen-vacancy-rich copper-based nanomaterial according to the above embodiment of the present invention may also have the following additional technical features:
[0008] In some embodiments of the present invention, the alcohol solvent is a C2-C3 alcohol substance, and the volume fraction of the alcohol substance is 10%-20%, and optimally 15%.
[0009] In some embodiments of the present invention, the alcohol solvent is one of ethanol, isopropanol or n-propanol, preferably isopropanol.
[0010] In some embodiments of the present invention, the copper salt is one or more of copper chloride, copper nitrate, copper acetate and copper sulfate, preferably copper sulfate; the concentration of the copper salt solution is 5 to 70 mmol / L; the time of the constant potential electrodeposition is 200 to 7200 s, preferably 2000 s and 3600 s, and most preferably 2000 s.
[0011] In some embodiments of the present invention, during the cyclic voltammetry current modification, the electrolyte solute used is one of potassium sulfate, sodium hypophosphite or potassium bicarbonate, preferably potassium sulfate, and the concentration of the electrolyte solute is 0.1 to 1 mol / L, most preferably 1 mol / L.
[0012] In some embodiments of the present invention, the number of cycles of the cyclic voltammetry current modification process is 20 to 80 times, and optimally 20 times.
[0013] In another aspect of the present invention, the present invention provides an oxygen-rich vacancy copper-based nanomaterial prepared according to the preparation method of the oxygen-rich vacancy copper-based nanomaterial.
[0014] In addition, the oxygen-vacancy-rich copper-based nanomaterial according to the above embodiment of the present invention may also have the following additional technical features:
[0015] In some embodiments of the present invention, the oxygen-vacancy-rich copper-based nanomaterial is broken irregular polyhedral particles.
[0016] In some embodiments of the present invention, the particle size of the oxygen-vacancy-rich copper-based nanomaterial is 1 to 2 μm.
[0017] In another aspect of the present invention, the present invention provides an application of an oxygen-vacancy-rich copper-based nanomaterial. According to an embodiment of the present invention, the oxygen-vacancy-rich copper-based nanomaterial is used to catalyze the carbon dioxide electroreduction reaction.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The preparation method of the oxygen-rich vacancy Cu / Cu2O nanomaterial of the present invention is to use an alcohol solvent dispersed in a copper salt solution with a certain volume fraction as an electrodeposition plating solution under neutral conditions, and deposit the copper component on a hydrophobic carbon paper by a constant potential deposition method. After the deposition process is completed, the material is transferred to a cyclic voltammetry current modification electrolyte for current modification to cause changes on the surface of the Cu site. This process is simple in technology, mild in conditions, green and environmentally friendly, and easy to achieve large-scale production.
[0020] (2) The oxygen-vacancy-rich Cu / Cu2O material of the present invention is broken polyhedral particles with uniform particle size, and the particle size range can be 1 to 2 μm.
[0021] (3) When the oxygen-rich Cu / Cu2O nanomaterials of the present invention are applied to the CO2RR reaction, they can promote the generation and adsorption of the intermediate *CO, which is beneficial to the CC coupling, thereby increasing the C 2+ It can not only improve the selectivity of the product, but also greatly inhibit the production of CO side reactions.
[0022] (4) In a preferred embodiment of the present invention, oxygen-rich Cu / Cu2O nanomaterials are used in the C 2+ Product Faraday efficiency FE C2+ The maximum value can reach 77.4%. At the same time, the reaction of producing CO byproduct is greatly suppressed, and the Faraday efficiency of producing CO is FE CO The minimum can be as low as 4.5%.
[0023] (5) The preparation process of the oxygen-rich Cu / Cu2O nanomaterial of the present invention is simple. The material prepared by copper salt grows directly on the base hydrophobic carbon paper without subsequent spraying treatment. In addition, abundant oxygen vacancies can be formed without calcination and other operations. The electrodeposition and cyclic voltammetry current modification process do not require stirring and can be carried out at room temperature without additional heating process.
[0024] (6) The electrodeposition process of the present invention can achieve the attachment of copper particles on the surface of the hydrophobic carbon paper, forming a particle deposition of Cu and Cu2O in a mixed valence state, and the cyclic voltammetry process can quickly reduce a portion of the Cu2O component to Cu, and oxygen atoms are quickly lost without copper atoms to supplement the collapsed lattice, thereby forming oxygen vacancies. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a scanning electron microscope (SEM) image of the oxygen vacancy-rich Cu / Cu2O material prepared in Example 3 of the present invention;
[0026] Figure 2 This is a scanning electron microscope (SEM) image of the Cu / Cu2O material prepared in Comparative Example 1 of the present invention;
[0027] Figure 3 This is an X-ray diffraction (XRD) pattern of the oxygen-vacancy-rich Cu / Cu2O material of Example 3 of the present invention;
[0028] Figure 4 X-ray photoelectron spectra (XPS) of the oxygen vacancy-rich Cu / Cu2O material of Example 3 of the present invention and the Cu / Cu2O material of Comparative Example 1, wherein (a) is the Cu 2P electron spectrum of Example 3, (b) is the Cu LMN Auger electron spectrum of Example 3, (c) is the Cu 2P electron spectrum of Comparative Example 1, and (d) is the Cu LMN Auger electron spectrum of Comparative Example 1;
[0029] Figure 5 The X-ray photoelectron spectroscopy (XPS) diagram of the Cu / Cu2O materials prepared in Example 3 and Comparative Example 1 of the present invention, wherein: Figure 5 (a) is the O1s electron spectrum of Example 3, Figure 5 (b) is the O1s electron spectrum of Comparative Example 1;
[0030] Figure 6 The electron magnetic resonance (EPR) spectra of the Cu / Cu2O materials prepared in Example 3 and Comparative Example 1 of the present invention are shown in FIG.
[0031] Figure 7 This is a Faraday efficiency diagram of gas phase products at different potentials of the oxygen vacancy-rich Cu / Cu2O material prepared by using Examples 1 to 5 in Example 11 of the present invention;
[0032] Figure 8 This is a Faraday efficiency diagram of gas phase products at different potentials of the oxygen vacancy-rich Cu / Cu2O material prepared by using Example 3 and Examples 6 to 10 in Example 11 of the present invention;
[0033] Fig. 9 The Cu / Cu2O materials prepared by using Example 3 and Comparative Example 1 in Example 11 of the present invention are C 2+ Product Faraday efficiency distribution diagram;
[0034] Fig.10 This is a Faraday efficiency diagram of CO at different current densities for the Cu / Cu2O material prepared using Example 3 and Comparative Example 1 in Example 11 of the present invention;
[0035] Fig.11 In Example 11 of the present invention, the Cu / Cu2O materials prepared by Example 3 and Comparative Example 1 are subjected to different current densities. 2+ Distribution diagram of the ratio of the Faradaic efficiency of the products to the Faradaic efficiency of CO. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] A method for preparing an oxygen-vacancy-rich copper-based nanomaterial comprises the following steps:
[0039] (1) Prepare electrolyte: thoroughly mix 2.5 mL of 0.1 mol / L copper sulfate solution (CuSO4), 40 mL of deionized water and 7.5 mL of isopropanol to a volume of 50 mL.
[0040] (2) A three-electrode system was used as the electrodeposition process reaction, the working electrode was 28-bc hydrophobic carbon paper, and the counter electrode was an electrode with an area of 1×1 cm 2 The platinum mesh electrode is a silver-silver chloride electrode as the reference electrode, and the mixed solution obtained in step (1) is an electrolyte. The electrodeposition process adopts constant potential deposition, the deposition potential is -0.32V (vs Ag / AgCl) and the deposition time is 2000s.
[0041] (3) After the electrodeposition process, the catalyst was transferred to a 1 mol / L potassium sulfate solution, and a CV scan was performed in a potential window of -0.3 to -0.8 V (vsAg / AgCl) at a scan rate of 50 mV / s to create oxygen vacancy active sites. The number of scan cycles was 20. The catalyst was dried in a room environment for 24 h to obtain the oxygen vacancy-rich Cu / Cu2O material.
[0042] Example 2
[0043] A method for preparing an oxygen-vacancy-rich copper-based nanomaterial, which differs from Example 1 only in that the volume of the copper sulfate solution is 5 ml and the volume of the deionized water is 37.5 ml.
[0044] Example 3
[0045] A method for preparing an oxygen-vacancy-rich copper-based nanomaterial, which differs from Example 1 only in that the volume of the copper sulfate solution is 15 ml and the volume of the deionized water is 7.5 ml.
[0046] The product obtained in Example 3 was characterized by XRD using a D8ADVANCE (Bruker) X-ray diffractometer. Figure 3 As shown. Figure 3 It can be seen that the main diffraction peaks correspond to the (111), (200) and (220) crystal planes of Cu2O (JCPDS 05-0667) and the (111), (200) and (220) of Cu (JCPDS 04-0836), proving that the product obtained in Example 3 is a mixed phase crystal of Cu and Cu2O.
[0047] Example 4
[0048] A method for preparing an oxygen-vacancy-rich copper-based nanomaterial, which differs from Example 1 only in that the volume of the copper sulfate solution is 25 ml and the volume of the deionized water is 17.5 ml.
[0049] Example 5
[0050] A method for preparing an oxygen-vacancy-rich copper-based nanomaterial, which differs from Example 1 only in that the volume of the copper sulfate solution is 35 ml and the volume of the deionized water is 7.5 ml.
[0051] Example 6
[0052] A method for preparing an oxygen-vacancy-rich copper-based nanomaterial, which differs from Example 3 only in that the electrodeposition time in step (2) is 200 s.
[0053] Example 7
[0054] A method for preparing an oxygen-vacancy-rich copper-based nanomaterial, which differs from Example 3 only in that the electrodeposition time in step (2) is 500 s.
[0055] Example 8
[0056] A method for preparing an oxygen-vacancy-rich copper-based nanomaterial, which differs from Example 3 only in that the electrodeposition time in step (2) is 1000 s.
[0057] Example 9
[0058] A method for preparing an oxygen-vacancy-rich copper-based nanomaterial, which differs from Example 3 only in that the electrodeposition time in step (2) is 3600 s.
[0059] Example 10
[0060] A method for preparing an oxygen-vacancy-rich copper-based nanomaterial, which differs from Example 3 only in that the electrodeposition time in step (2) is 7200 s.
[0061] Comparative Example 1
[0062] After the electrodeposition in step (2) of Example 1 is completed, there is no subsequent cyclic voltammetry current modification process, and the remaining steps and conditions are the same as in Example 1.
[0063] The S-4800 instrument was used to perform SEM micromorphology characterization on the products obtained in Example 3 and Comparative Example 1. The results are as follows: Figure 1 and Figure 2 As shown. Figure 1 It can be seen that the product prepared by Example 3 has a particle size of 1-2 μm and is a broken polyhedron. Figure 2 It can be seen that the product particles prepared by Comparative Example 1 are basically the same as the particles prepared by Example 3.
[0064] The products obtained in Example 3 and Comparative Example 1 were characterized by X-ray photoelectron spectroscopy (XPS) using Thermo Scientific ESCALAB 250Xi. The results are as follows: Figure 4 As shown. Figure 4 The Cu 2p electron spectrum results in (a) show that Cu2O (Cu + ) or Cu(Cu 0 ) and CuO at 935 eV. + / Cu 0 Oxidation. Figure 4 (b) Cu LMM Auger electron spectroscopy (AES) shows that the Cu element in the product is mainly in the monovalent oxidation state (Cu at 570 eV). +characteristic peak) and zero valence state (Cu at 568 eV 0 The XPS characterization results show that the product obtained in Example 3 is a mixture of Cu and Cu2O. Figure 4 (c) and Figure 4 As shown in (d), Comparative Example 1 also presents a mixed valence state of Cu and Cu2O.
[0065] The product obtained in Example 3 was characterized by X-ray photoelectron spectroscopy (XPS) using Thermo Scientific ESCALAB 250Xi. The results are as follows: Figure 5 As shown, the oxygen vacancy peak of Example 3 (O v The oxygen vacancy characteristic peak of the comparative example 1 is higher than that of the comparative example 1. The overall oxygen vacancy content is measured by parasitic electron magnetic resonance (EPR), such as Figure 6 The oxygen vacancy content of Example 3 is also greater than that of Comparative Example 1.
[0066] Embodiment 11
[0067] A method for electrocatalytic CO2 reduction (CO2RR) comprising the following steps:
[0068] Electrocatalysis was performed in a standard three-electrode system using an Autolab 302N electrochemical workstation. The oxygen-vacancy-rich Cu / Cu2O nanomaterials prepared in Examples 1-10 were used as the working electrode for the CO2RR reaction. Ag / AgCl was used as the reference electrode and Ni foam was used as the counter electrode (geometric area of 0.8×1.7 cm 2 ), using a flow cell electrolytic cell for reaction. The cathode chamber and the anode chamber of the electrolytic cell are separated by an anion exchange membrane, and the electrolytes in the anode chamber and the cathode chamber are both 1.0 mol / L potassium bicarbonate solution, and the flow rate is 5 ml / min.
[0069] The gaseous products produced by catalytic CO2RR were quantitatively analyzed using an online gas chromatography system (Shanghai Ruimin, GC-2060) equipped with a FID detector. 1 H NMR) was used to sample and analyze the liquid product in the electrolyte after CO2 electrolysis reduction, and the spectrum was collected on a Bruker AM 400 spectrometer using dimethyl sulfoxide (DMSO) as the internal standard. The oxygen-rich Cu / Cu2O nanomaterials prepared in Examples 1 to 10 were respectively heated at -300 mA / cm 2 The current density of the five tests was -200 mA / cm 2 、-250mA / cm 2、-300mA / cm 2 、-350mA / cm 2 and -400mA / cm 2 .
[0070] According to the above method, the CO2RR test was carried out using the catalysts of Examples 1 to 5, and the Faraday efficiency of the gas phase product was obtained as follows: Figure 7 As shown, the gas phase products obtained by using the catalysts of Examples 3 and Examples 6 to 10 are as follows Figure 8 The five current densities C of Example 3 and Comparative Example 1 are shown. 2+ The product Faraday efficiency is Fig. 9 As shown, the CO Faraday efficiency at five current densities of Example 3 and Comparative Example 1 is as follows Fig.10 As shown, C of Example 3 2+ Compared with the amount of CO produced Fig.11 shown.
[0071] Depend on Figure 7 and Figure 8 It can be seen that the catalyst obtained in Example 3 has higher performance. Fig. 9 and Fig.10 It can be seen that the catalyst C of Example 3 with rich oxygen vacancies 2+ The maximum Faraday efficiency can reach 77.5%; the CO Faraday efficiency is 4.5%, which is lower than that of comparative example 1. Fig.11 It can be seen that the catalyst C in Example 3 2+ The ratio to CO can reach up to 26, which is much higher than the catalyst in Comparative Example 1.
[0072] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing oxygen-vacancy-rich copper-based nanomaterials, characterized in that: The following steps are involved: In the case of alcohol solvents as hydrophilic agents, copper salt solution is used as electrolyte, constant potential electrodeposition is carried out on the surface of hydrophobic carbon paper, and the electrolyte is replaced for cyclic voltammetry current modification, wherein the potential window of the cyclic voltammetry process is -0.3 to -0.8V.
2. The method for preparing an oxygen-vacancy-rich copper-based nanomaterial according to claim 1, characterized in that: The alcohol solvent is a C2-C3 alcohol substance, and the volume fraction of the alcohol substance is 10%-20%.
3. The method for preparing an oxygen-rich vacancy copper-based nanomaterial according to claim 1, characterized in that: The alcohol solvent is one of ethanol, isopropanol or n-propanol.
4. The method for preparing an oxygen-vacancy-rich copper-based nanomaterial according to claim 1, characterized in that: The copper salt is one or more of copper chloride, copper nitrate, copper acetate and copper sulfate. The concentration of the copper salt solution is 5-70 mmol / L. The constant potential electrodeposition time is 200-7200 s.
5. The method for preparing an oxygen-vacancy-rich copper-based nanomaterial according to claim 1, characterized in that: During the cyclic voltammetry current modification, the electrolyte solute used is one of potassium sulfate, sodium hypophosphite or potassium bicarbonate, and the concentration of the electrolyte solute is 0.1-1 mol / L.
6. The method for preparing an oxygen-vacancy-rich copper-based nanomaterial according to claim 1, characterized in that: The number of cycles of the cyclic voltammetry current modification process is 20 to 80 times.
7. An oxygen-rich vacancy copper-based nanomaterial prepared according to the method for preparing oxygen-rich vacancy copper-based nanomaterials according to claims 1-6.
8. The oxygen vacancy-rich copper-based nanomaterial according to claim 7, characterized in that: The oxygen-vacancy-rich copper-based nanomaterial is broken irregular polyhedral particles.
9. The oxygen-vacancy-rich copper-based nanomaterial according to claim 8, characterized in that: The particle size of the oxygen-rich vacancy copper-based nanomaterial is 1 to 2 μm.
10. An application of the oxygen-vacancy-rich copper-based nanomaterial according to claim 7, characterized in that: The oxygen-vacancy-rich copper-based nanomaterial is used for catalyzing the carbon dioxide electroreduction reaction.
Citation Information
Cited By
Copper-based vesicle multistage composite electrocatalyst, preparation method thereof and application of copper-based vesicle multistage composite electrocatalyst in electroreduction of carbon dioxide
CN122648982A